Influencing factors for anterior tibial artery atherosclerosis among patients with hyperuricemia - SUN Lu, ZHENG Dong, ZHANG Hongchao (预防医学)
Objective: To analyze the influencing factors for anterior tibial artery atherosclerosis among patients with hyperuricemia, so as to provide insights into the prevention of anterior tibial artery atherosclerosis. Methods: Patients aged 18 years and older with hyperuricemia in Dazhou Integrated TCM & Western Medicine Hospital were enrolled as research subjects from 2020 to 2023. Demographic information and blood biochemistry indicators were collected through electronic medical records. Anterior tibial artery atherosclerosis was evaluated by color Doppler ultrasound. Factors affecting anterior tibial artery atherosclerosis among patients with hyperuricemia were analyzed by a multivariable logistic regression model. Results: A total of 1 105 patients with hyperuricemia were surveyed, including 862 males (78.01%) and 243 females (21.99%). There were 918 cases (83.08%) at the ages of 60 years and older, and 457 cases (41.36%) with a course of disease at 10 years and longer. The median level of blood uric acid was 480.79 (interquartile range, 98.28) μmol/L. There were 314 cases (28.42%) with anterior tibial artery atherosclerosis. Multivariable logistic regression analysis showed that body mass index (≥24.0 kg/m2, OR=1.597, 95%CI: 1.185-2.151), long-term smoking history (yes, OR=1.709, 95%CI: 1.153-2.534), diabetes mellitus (yes, OR=1.517, 95%CI: 1.162-1.981), serum uric acid (≥480.79 μmol/L, OR=1.667, 95%CI: 1.131-2.457), serum creatinine (≥97 μmol/L, OR=1.685, 95%CI: 1.155-2.460), fasting blood glucose (≥6.1 mmol/L, OR=1.528, 95%CI: 1.106-2.112), fibrinogen (>4 g/L, OR=1.589, 95%CI: 1.091-2.315) and triglycerides (≥1.7 mmol/L, OR=1.879, 95%CI: 1.226-2.881) were influencing factors for anterior tibial artery atherosclerosis among patients with hyperuricemia. Conclusion: Anterior tibial artery atherosclerosis among patients with hyperuricemia is associated with long-term smoking, diabetes mellitus, serum uric acid, serum creatinine, fasting blood glucose, fibrinogen and triglycerides high level.